IMPLEMENTASI ATAS DESENTRALISASI PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) (Studi Kasus pada Dinas Pendapatan Daerah Kota Madiun dan Kantor Pelayanan Pajak Pratama Madiun) - Megawati, Retno (Jurnal Mahasiswa Perpajakan, 2015)
Madiun is one of the cities that decentralized Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) at the time of deadline, in January 1, 2014. As we know that DJP’s data are 123 cities that have decentralized PBB-P2 before January 1, 2014. It shows that if a city can prepare well, they can decentralized PBB-P2 before the deadline. This research focused on the implementation, obstacles are happened, and result of decentralization of PBB-P2. The result of this research is Dispenda Kota Madiun has complete provision of Article 5 paragraph (1) in the Joint Regulation of the Minister of Finance and Minister of Home No. 15/PMK.07/2014 and No. 10 of 2014 about The Steps of Preparation and Implementation of PBB-P2. Dispenda Kota Madiun has been ready to manage it, but some tools like plotter and software runtime applications are unvailable. Some of obstacles that occured are not online system in Kelurahan and complaint of Taxpayers about centralization of payments at Perception Bank. Keywords: Implementation, Decentralization, PBB-P2